Does dietary intake of acrylamide affect hydroxyproline levels? An animal study - Tugba Agbektas; Ozhan Pazarci; Ayca Tas; Nese Keklikcioglu Cakmak; Seyran Kilinc; Yavuz Silig (Medicine Science, 2022)
Acrylamide is a chemical that occurs due to high temperatures during cooking. It consists of an amino acid found in foods and sugars. Studies have shown that cancer formation occurs within the scope of oxidant reagents and DNA damage due to exposure to acrylamide. Our study aims to examine the effects of dietary acrylamide intake on plasma hydroxyproline levels in rats. In this study, 4 groups were formed with 8 rats in each group (total number=32). Blood samples were collected on days 14 and 28. Acrylamide solution was applied to each rat in the treatment group by gastric gavage process at 5 mg/kg three times a week. Hydroxyproline levels in rats' plasma samples were measured. The median (IQR) hydroxyproline levels were 7.40(2.45) µg/L in group 1 (14. days control group) and 7.98(3.34) µg/L in group 2 (14. days acrylamide applied) who received acrylamide. The mean hydroxyproline levels were 7.25(1.96) µg/L in group 3 (28. days control group) and 9.76(2.64) µg/L in group 4 (28. days acrylamide applied) who received acrylamide. No difference was observed between the groups. Dietary acrylamide intake did not have a significant effect on hydroxyproline levels at the application dose and duration in our study. [Med-Science 2022; 11(4.000): 1478-81]